Hak Cipta Logo Yang Didaftarkan Sebagai Merek - Lopulalan, Yunus Marlon; Akyuwen, Rory Jeff; Pariela, Marselo Valentino Geovani (Faculty of Law, Universitas Pattimura, 2021)
Introduction: Copyright protection is carried out in order to prevent infringement of copyright itself. Copyright holders can be distinguished between individuals and legal entities. The logo is protected in Law Number 28 of 2014 concerning Copyright and Law Number 20 of 2016 concerning Trademarks and Geographical Indications. However, the logo is prohibited from being recorded in Article 65 of the Copyright Law of 2014 so that the logo can only be registered as a trademark.Purposes of the Research: Knowing and analyzing the regulatory and legal status of Logo Copyrights registered as Trademarks.Methods of the Research: This study uses a normative juridical method with legal materials used in the study are primary, secondary and tertiary with the use of literature study techniques in the form of international legal regulations, scientific papers and literature.Results of the Research: Logo copyright as a mark that serves as a differentiator can no longer be registered. The recording of a work cannot be made on painting in the form of a logo or distinguishing mark that is used as a mark in trading in goods / services or is used as a symbol of an organization, business entity or legal entity. So as a measure to anticipate violations of the logo creator's rights, the logo can be registered as a trademark. Material rights can also be attached to the copyright of the logo used as a brand.